A single crystal lithium-rich manganese-based positive electrode material and preparation method thereof and lithium-ion battery
By selecting the appropriate M and N elements, adjusting the element ratio, and using co-precipitation technology and high-temperature sintering technology, a single crystal lithium-rich manganese-based cathode material with high compaction density and low specific surface area is prepared, which solves the problems of existing materials in cycling performance and voltage attenuation, and achieves higher volume energy density and cycle life.
Patent Information
- Application Number
- CN202410075792.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-18
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-01-18
AI Technical Summary
The existing lithium-rich manganese-based cathode materials have problems in cycling performance and voltage attenuation, and their structural collapse and electrochemical performance collapse make it difficult to achieve commercial application and industrialization.
By selecting suitable M and N elements, adjusting the dosage ratio of each element, using co-precipitation technology and high-temperature sintering technology, a single crystal lithium-rich manganese-based positive electrode material is prepared to form single crystal particles with high compaction density and low specific surface area.
The high compaction density and low specific surface area of single crystal lithium-rich manganese-based positive electrode material are achieved, which inhibits interfacial side reactions and improves volume energy density and cycle life.
Smart Images

Figure CN118099409B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a single crystal lithium-rich manganese-based positive electrode material and a preparation method thereof, and a lithium ion battery. Background Art
[0002] High specific energy, low cost and high safety are important technical breakthroughs for the long-term sustainable and healthy development of the lithium-ion battery industry. They are also a strong guarantee for achieving efficient resource utilization and strengthening the quality of the industrial chain, which is in line with the dual-carbon development concept. The positive electrode material accounts for 40-50% of the quality and cost of lithium-ion batteries, which largely determines the key performance of the battery, such as energy density, safety and life. Lithium-rich manganese-based positive electrode materials have low raw material costs, high thermal stability and a specific capacity of more than 250mAh / g. They are regarded as the preferred materials to support the upgrading of lithium battery technology in the near future. However, technical difficulties such as poor cycle performance, fast voltage decay and low compaction density have not been overcome for a long time, which has hindered its commercial application and industrialization process.
[0003] At present, the mainstream lithium-rich manganese-based cathode materials are secondary spherical cathode particles formed by random orientation and agglomeration of nano-scale primary particles. During the process of lithium insertion and extraction, the cathode particles continue to expand and shrink, and the stress is easily concentrated at the grain boundary and microcracks appear, resulting in particle breakage and pulverization, causing the collapse of the material structure and the collapse of electrochemical performance; at the same time, polycrystalline particles have more electrode-electrolyte interfaces, and their adverse side reactions are more; on the other hand, there are more pores on the surface and inside of the secondary particles, which will reduce the compaction density of the material. Studies have shown that single crystal materials have many advantages such as fewer reaction interfaces, high compaction density, strong structural stability, and good safety. Single crystalization has become an important technical direction for cathode materials. The main synthesis method of single crystal lithium-rich manganese-based cathode materials is the high-temperature solid phase method, which usually uses precursors and excess lithium salts, and adds a large amount of flux (molten salt). Keeping the temperature at high temperature for a certain period of time promotes the continuous growth of crystal particles, but the product is usually severely agglomerated, and it is difficult to form monodispersed single crystal particles. At the same time, the adverse doping of the flux, subsequent cleaning and corrosion of the equipment are difficult to solve. For example, the Chinese patent with publication number CN116143200A uses a co-precipitated precursor, a lithium source, and a molten salt mixture to obtain a single-crystal lithium-rich manganese-based material with a high compaction density by a step-by-step lithium preparation, calcination, and suction filtration and washing method. The single crystal structure is good and the performance is excellent, but the process is relatively complicated. The Chinese patent with publication number CN116632218A uses a high-temperature solid phase method to obtain a monodispersed single-crystal lithium-rich manganese-based positive electrode material. The precursor, lithium salt, flux, additive, etc. are also required to be washed and sintered again after high-temperature sintering. The Chinese patent with publication number CN116623295A discloses a tantalum-zirconium co-doped cobalt-free single-crystal lithium-rich manganese-based positive electrode material and its preparation method. The single-crystal lithium-rich manganese-based material is obtained by a one-step method of ball milling mixing and high-temperature sintering. The process method is relatively simple, but the single crystal particle size is relatively small and the dispersibility is poor. Summary of the invention
[0004] In order to solve the above technical problems, the present invention proposes a single crystal lithium-rich manganese-based positive electrode material and a preparation method thereof and a lithium-ion battery, which can obtain a micron-level single crystal lithium-rich manganese-based positive electrode material with good crystal structure, monodispersity and uniform size.
[0005] According to a first aspect of the present invention, the present invention provides a single crystal lithium-rich manganese-based positive electrode material, the chemical formula of the positive electrode material is Li x Mn a Ni b Co c M d N e O g , wherein M is one of W, Mo, La, Zr, Nb, Ta, V, and Hf, N is one of F, B, Cl, Br, S, and P, 1<x≤1.3, 0.5<a≤0.8, 0.1≤b<0.5, 0<c≤0.5, 0<d≤0.1, 0<e≤0.1, 2≤g<2.2, and 0.1≤d / e≤5.
[0006] The single crystal lithium-rich manganese-based positive electrode material of the present invention comprises Li element, Mn element, Ni element, Co element, M element, N element and O element, wherein the M element has the function of refining grains, and the N element has the function of assisting sintering. The M element and the N element are specifically selected, and the dosage ratio between the elements is adjusted at the same time, so that a synergistic effect is achieved between the elements, so that the obtained positive electrode material forms a single crystal morphology, has a high compaction density and a low specific surface area, thereby reducing the contact surface between the positive electrode material and the electrolyte, thereby inhibiting the interface side reaction, and improving the volume energy density and cycle life of the lithium-rich manganese-based positive electrode material.
[0007] In order to maximize the compaction density of the positive electrode material and reduce the specific surface area of the positive electrode material, further, 1<x≤1.2, 0.5<a≤0.6, 0.1≤b<0.3, 0.1<c≤0.15, 0.01≤d≤0.05, 0.01≤e≤0.07.
[0008] Furthermore, the positive electrode material satisfies at least one of the following characteristics (1)-(4):
[0009] (1) The positive electrode material has a lithium-rich layered phase crystal structure;
[0010] (2) The morphology of the positive electrode material is monodispersed single crystal particles with a median particle size D 50 1μm-10μm;
[0011] (3) The specific surface area of the positive electrode material is ≤1m 2 / g;
[0012] (4) The compaction density of the positive electrode material is 3.0 g / cm 3 -3.6g / cm 3 .
[0013] According to a second aspect of the present invention, the present invention also provides a method for preparing the above-mentioned positive electrode material, comprising the following steps:
[0014] Step (1): dissolving a soluble manganese salt, a soluble nickel salt and a soluble cobalt salt in water to prepare a metal salt solution according to the chemical formula of the positive electrode material, controlling the temperature and pH value of the reaction system, adding a precipitant and a complexing agent to carry out a precipitation reaction, and washing, filtering and drying after the precipitation reaction to obtain a lithium-rich manganese-based precursor;
[0015] Step (2): weighing corresponding amounts of the lithium-rich manganese-based precursor, the first additive containing the M element, the second additive containing the N element and the lithium source according to the chemical formula, mixing them evenly and then pressing to obtain a mixture; wherein, if d+e in the chemical formula of the positive electrode material is ≥0.08, at least two lithium sources need to be added, and the at least two lithium sources include a first lithium source and a second lithium source;
[0016] Step (3): sintering the mixture obtained in step (2) at high temperature to obtain the positive electrode material.
[0017] In the above scheme, the preparation method of the positive electrode material first adopts the coprecipitation technology to prepare a lithium-rich manganese-based precursor, and then the lithium-rich manganese-based precursor, the first additive containing the M element, the second additive containing the N element and the lithium source are mixed evenly and pressed into particles or sheets of a specified shape and size to adapt to the subsequent sintering process, which is beneficial to improve the density of the positive electrode material after sintering, and regulate the microstructure and grain size of the positive electrode material, thereby improving the electrochemical performance of the positive electrode material. Further, if d+e≥0.08, it is necessary to add the first lithium source and the second lithium source at the same time. This is because if the addition amount of the M and N elements is too high, the crystal structure of the synthesized target material has a heterogeneous phase. After a large number of experiments, it is found that the addition of the second lithium source can effectively eliminate the heterogeneous phase and form a lithium-rich manganese-based positive electrode material with a complete crystal structure and good single crystal morphology, which is beneficial to the improvement of the compaction density of the positive electrode material and the reduction of the specific surface area, thereby improving the volume energy density and cycle life of the lithium-rich manganese-based positive electrode material. The preparation method of the present invention does not require the use of a large amount of flux and subsequent washing processes used in traditional processes. The prepared single crystal material has good dispersibility and uniform particle size distribution, is easy to scale up in batches, and can be used for industrial production.
[0018] Furthermore, in step (2), the first lithium source is at least one of lithium carbonate, lithium hydroxide, and lithium chloride;
[0019] And / or, the second lithium source is lithium nitrate;
[0020] and / or, in terms of Li, the molar ratio of the amount of the lithium source added to the amount of the lithium-rich manganese-based precursor is 1:1 to 1.3:1;
[0021] and / or, if d+e≥0.08, the molar ratio of the first lithium source to the second lithium source is 0.05-0.5, calculated as Li;
[0022] And / or, if d+e<0.08, the second lithium source does not need to be added in step (2).
[0023] Furthermore, in step (2), the pressing pressure is ≥ 0.05 mPa.
[0024] Further, in step (2), the first additive containing the M element is one of tungsten oxide, molybdenum oxide, lanthanum oxide, zirconium oxide, niobium oxide, tantalum oxide, vanadium oxide, hafnium oxide, lithium tungstate, lithium molybdate, lithium lanthanate, lithium zirconate, lithium niobate, lithium tantalate, and lithium vanadate;
[0025] And / or, the second additive containing the N element is one of lithium fluoride, ammonium fluoride, boric acid, ammonium chloride, boron oxide, ammonium bromide, ammonium sulfate, and ammonium phosphate.
[0026] Furthermore, in step (3), the high-temperature sintering atmosphere is an oxygen-containing atmosphere, and the sintering system is firstly to increase the temperature to 400°C-700°C at a rate of 0.1°C / min-10°C / min, keep the temperature for 2h-10h, then to increase the temperature to 800°C-1100°C at a rate of 0.1°C / min-10°C / min, keep the temperature for 5h-20h, and then naturally cool, crush and sieve to obtain the positive electrode material.
[0027] Furthermore, in step (1), the soluble manganese salt includes one or more of sulfate, nitrate, acetate and chloride of manganese;
[0028] And / or, the soluble nickel salt includes one or more of the sulfate, nitrate, acetate and chloride of nickel;
[0029] And / or, the soluble cobalt salt includes one or more of sulfate, nitrate, acetate and chloride of the cobalt element;
[0030] And / or, the precipitant is at least one of sodium hydroxide, potassium hydroxide, sodium carbonate and potassium carbonate;
[0031] And / or, the complexing agent is at least one of ammonia, citric acid, and oxalic acid;
[0032] and / or, the precipitation reaction temperature is 40-70°C;
[0033] And / or, when the precipitant is sodium carbonate or potassium carbonate, the pH value of the precipitation reaction is 6-9, and when the precipitant is sodium hydroxide or potassium hydroxide, the pH value of the precipitation reaction is 9-12.
[0034] According to the third aspect of the present invention, the present invention further provides a lithium ion battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the positive electrode material mentioned above or the positive electrode material prepared by the above preparation method.
[0035] Beneficial effects of the present invention:
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] (1) The present invention obtains a single-crystal lithium-rich manganese-based positive electrode material with a compaction density of up to 3.6 g / cm 3 The minimum specific surface area is only 0.25m 2 / g, which can greatly reduce the contact area between the positive electrode material and the electrolyte, thereby inhibiting the interfacial side reactions and improving the volume energy density and cycle life of the lithium-rich manganese-based positive electrode material.
[0038] (2) The present invention develops a simple method for preparing a single-crystal lithium-rich manganese-based positive electrode material, which does not require the use of a large amount of flux and subsequent washing process used in traditional processes. The synthesized single-crystal material has good dispersibility and uniform particle size distribution, is easy to scale up in batches, and can be used for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0040] Figure 1 X-ray diffraction patterns of the positive electrode materials of Examples 1 and 2 of the present invention;
[0041] Figure 2 This is a SEM image of the positive electrode material of Example 1 of the present invention;
[0042] Figure 3 This is a SEM image of the positive electrode material of Example 2 of the present invention;
[0043] Figure 4 This is a SEM image of the positive electrode material of Example 3 of the present invention;
[0044] Figure 5 X-ray diffraction patterns of the positive electrode materials of Example 3 and Comparative Example 4 of the present invention;
[0045] Figure 6 X-ray diffraction pattern of the positive electrode material of Comparative Example 1 of the present invention;
[0046] Figure 7 SEM image of the positive electrode material of Comparative Example 1 of the present invention;
[0047] Figure 8 X-ray diffraction pattern of the positive electrode material of Comparative Example 2 of the present invention;
[0048] Fig. 9 SEM image of the positive electrode material of Comparative Example 2 of the present invention;
[0049] Fig.10 SEM image of the positive electrode material of Comparative Example 3 of the present invention;
[0050] Fig.11 SEM image of the positive electrode material of Comparative Example 4 of the present invention;
[0051] Fig.12 SEM image of the positive electrode material of Comparative Example 5 of the present invention;
[0052] Fig.13 The first charge and discharge curves of the batteries prepared with the positive electrode materials of Example 1, Example 2 and Comparative Example 1 of the present invention;
[0053] Fig.14 Cycling performance curves of batteries prepared from the positive electrode materials of Example 1, Example 2 and Comparative Example 1 of the present invention;
[0054] Fig.15 The first charge and discharge curves of the batteries prepared with the positive electrode materials of Example 3 and Comparative Example 4 of the present invention;
[0055] Fig.16 Cycling performance curves of batteries prepared with the positive electrode materials of Example 3 and Comparative Example 4 of the present invention. DETAILED DESCRIPTION
[0056] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0057] If no specific technology or conditions are specified in the examples and comparative examples, the technology or conditions described in the literature in the field or the product instructions are used. If the manufacturer of the instruments and the like is not specified, conventional products can be purchased through regular channels. The chemical raw materials used in the present invention can be easily purchased in the domestic chemical product market.
[0058] Example 1
[0059] This embodiment provides a single crystal lithium-rich manganese-based positive electrode material, whose chemical formula is Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 W 0.0 3F 0.02 O 2.085 .
[0060] The preparation method of the positive electrode material comprises the following steps:
[0061] Manganese sulfate monohydrate, nickel sulfate hexahydrate and cobalt sulfate heptahydrate were weighed in a molar ratio of 0.54:0.13:0.13, and dissolved in deionized water to prepare a 2 mol / L metal salt solution A; sodium hydroxide was dissolved in water to prepare a 2 mol / L precipitant solution B. Under stirring conditions of 500 rpm / min, solutions A and B were slowly added dropwise to deionized water. The pH value of the reaction system was controlled to be 11.5 and the system temperature was 55°C. After reacting for 20 hours, the obtained precipitate was washed, filtered and dried to obtain a lithium-rich manganese-based precursor Mn 0.54 Ni 0.13 Co 0.13 (OH)2.
[0062] According to the chemical formula Li 1.2 Mn 0.54 Ni 0.13 C0 0.13 W 0.03 F 0.02 O 2.085 Weigh the corresponding amount of lithium-rich manganese-based precursor, lithium carbonate (in terms of Li), tungsten oxide (in terms of W), and ammonium fluoride, put the above materials into a high-speed mixer, mix them evenly and press them into sheets, place them in an atmosphere furnace for sintering, the sintering atmosphere is air, first heat up to 500°C at a heating rate of 3°C / min, keep warm for 5h, then continue to heat up to 950°C at the same rate, keep warm for 15h, and cool to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0063] Example 2
[0064] This embodiment provides a single crystal lithium-rich manganese-based positive electrode material, whose chemical formula is Li 1.2 Mn 0.54 Ni 0.13Co 0.13 W 0.0 3B 0.03 O 2.14 .
[0065] The preparation method of the positive electrode material comprises the following steps:
[0066] Manganese sulfate monohydrate, nickel sulfate hexahydrate and cobalt sulfate heptahydrate were weighed in a molar ratio of 0.54:0.13:0.13, and dissolved in deionized water to prepare a 2 mol / L metal salt solution A; sodium hydroxide was dissolved in water to prepare a 2 mol / L precipitant solution B. Under stirring conditions of 500 rpm / min, solutions A and B were slowly added dropwise to deionized water. The pH value of the reaction system was controlled to be 11.5 and the system temperature was 55°C. After reacting for 20 hours, the obtained precipitate was washed, filtered and dried to obtain a lithium-rich manganese-based precursor Mn 0.54 Ni 0.13 Co 0.13 (OH)2.
[0067] According to the chemical formula Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 W 0.03 B 0.03 O 2.14 Weigh the corresponding amount of lithium-rich manganese-based precursor, lithium carbonate (in terms of Li), tungsten oxide (in terms of W), and boric acid, put the above materials into a high-speed mixer, mix them evenly and press them into sheets, place them in an atmosphere furnace for sintering, the sintering atmosphere is air, first heat up to 500°C at a heating rate of 3°C / min, keep warm for 5h, then continue to heat up to 950°C at the same rate, keep warm for 15h, and cool to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0068] Example 3
[0069] This embodiment provides a single crystal lithium-rich manganese-based positive electrode material, whose chemical formula is Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 W 0.0 3B 0.05 O 2.17 .
[0070] The preparation method of the positive electrode material comprises the following steps:
[0071] Manganese sulfate monohydrate, nickel sulfate hexahydrate and cobalt sulfate heptahydrate were weighed in a molar ratio of 0.54:0.13:0.13, and dissolved in deionized water to prepare a 2 mol / L metal salt solution A; sodium hydroxide was dissolved in water to prepare a 2 mol / L precipitant solution B. Under stirring conditions of 500 rpm / min, solutions A and B were slowly added dropwise to deionized water. The pH value of the reaction system was controlled to be 11.5 and the system temperature was 55°C. After reacting for 20 hours, the obtained precipitate was washed, filtered and dried to obtain a lithium-rich manganese-based precursor Mn 0.54 Ni 0.13 Co 0.13 (OH)2.
[0072] According to the chemical formula Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 W 0.03 B 0.05 O 2.17 Weigh the corresponding amounts of lithium-rich manganese-based precursor, lithium carbonate (in terms of Li, accounting for 90% of the amount of lithium added), lithium nitrate (in terms of Li, accounting for 10% of the amount of lithium added), tungsten oxide (in terms of W), and boric acid, put the above materials into a high-speed mixer, mix them evenly and press them into sheets, place them in an atmosphere furnace for sintering, the sintering atmosphere is air, first heat up to 500°C at a heating rate of 3°C / min, keep warm for 5h, then continue to heat up to 950°C at the same rate, keep warm for 15h, and cool to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0073] Example 4
[0074] This embodiment provides a single crystal lithium-rich manganese-based positive electrode material, whose chemical formula is Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 La 0.03 B 0.03 O 2.095 .
[0075] The preparation method of the positive electrode material comprises the following steps:
[0076] Manganese sulfate monohydrate, nickel sulfate hexahydrate and cobalt sulfate heptahydrate were weighed in a molar ratio of 0.54:0.13:0.13, and dissolved in deionized water to prepare a 2 mol / L metal salt solution A; sodium hydroxide was dissolved in water to prepare a 2 mol / L precipitant solution B. Under stirring at 500 rpm / min, solutions A and B were slowly added dropwise to deionized water. The pH value of the reaction system was controlled to be 11.5 and the system temperature was 55°C. After reacting for 20 hours, the obtained precipitate was washed, filtered and dried to obtain a lithium-rich manganese-based precursor Mn. 0.54 Ni0.13 Co 0.13 (OH)2.
[0077] According to the chemical formula Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 La 0.03 B 0.03 O 2.095 Weigh the corresponding amount of lithium-rich manganese-based precursor, lithium hydroxide (in terms of Li), lanthanum oxide (in terms of La), and boric acid, put the above materials into a high-speed mixer, mix them evenly and press them into sheets, place them in an atmosphere furnace for sintering, the sintering atmosphere is air, first heat up to 500°C at a heating rate of 3°C / min, keep warm for 5 hours, then continue to heat up to 950°C at the same rate, keep warm for 15 hours, and cool to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0078] Example 5
[0079] This embodiment provides a single crystal lithium-rich manganese-based positive electrode material, whose chemical formula is Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 La 0.03 Cl 0.01 O 2.045 .
[0080] The preparation method of the positive electrode material comprises the following steps:
[0081] Manganese sulfate monohydrate, nickel sulfate hexahydrate and cobalt sulfate heptahydrate were weighed in a molar ratio of 0.54:0.13:0.13, and dissolved in deionized water to prepare a 2 mol / L metal salt solution A; sodium hydroxide was dissolved in water to prepare a 2 mol / L precipitant solution B. Under stirring at 500 rpm / min, solutions A and B were slowly added dropwise to deionized water. The pH value of the reaction system was controlled to be 11.5 and the system temperature was 55°C. After reacting for 20 hours, the obtained precipitate was washed, filtered and dried to obtain a lithium-rich manganese-based precursor Mn. 0.54 Ni 0.13 Co 0.13 (OH)2.
[0082] According to the chemical formula Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 La 0.03 Cl 0.01 O 2.045Weigh the corresponding amount of lithium-rich manganese-based precursor, lithium hydroxide (in terms of Li), lanthanum oxide (in terms of La), and ammonium chloride, put the above materials into a high-speed mixer, mix them evenly and press them into sheets, place them in an atmosphere furnace for sintering, the sintering atmosphere is air, first heat up to 500°C at a heating rate of 3°C / min, keep warm for 5h, then continue to heat up to 950°C at the same rate, keep warm for 15h, and cool to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0083] Example 6
[0084] This embodiment provides a single crystal lithium-rich manganese-based positive electrode material, whose chemical formula is Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 Mo 0.02 F 0.02 O 2.055 .
[0085] The preparation method of the positive electrode material comprises the following steps:
[0086] Manganese sulfate monohydrate, nickel sulfate hexahydrate and cobalt sulfate heptahydrate were weighed in a molar ratio of 0.54:0.13:0.13, and dissolved in deionized water to prepare a 2 mol / L metal salt solution A; sodium hydroxide was dissolved in water to prepare a 2 mol / L precipitant solution B. Under stirring at 500 rpm / min, solutions A and B were slowly added dropwise to deionized water. The pH value of the reaction system was controlled to be 11.5 and the system temperature was 55°C. After reacting for 20 hours, the obtained precipitate was washed, filtered and dried to obtain a lithium-rich manganese-based precursor Mn. 0.54 Ni 0.13 Co 0.13 (OH)2.
[0087] According to the chemical formula Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 Mo 0.02 F 0.02 O 2.055 Weigh the corresponding amount of lithium-rich manganese-based precursor, lithium carbonate (in terms of Li), molybdenum oxide (in terms of Mo), and ammonium fluoride, put the above materials into a high-speed mixer, mix them evenly and press them into sheets, place them in an atmosphere furnace for sintering, the sintering atmosphere is air, first heat up to 500°C at a heating rate of 3°C / min, keep warm for 5h, then continue to heat up to 950°C at the same rate, keep warm for 15h, and cool to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0088] Example 7
[0089] This embodiment provides a single crystal lithium-rich manganese-based positive electrode material, whose chemical formula is Li1.2 Mn 0.54 Ni 0.13 Co 0.13 Nb 0.02 F 0.02 O 2.045 .
[0090] The preparation method of the positive electrode material comprises the following steps:
[0091] Manganese sulfate monohydrate, nickel sulfate hexahydrate and cobalt sulfate heptahydrate were weighed in a molar ratio of 0.54:0.13:0.13, and dissolved in deionized water to prepare a 2 mol / L metal salt solution A; sodium hydroxide was dissolved in water to prepare a 2 mol / L precipitant solution B. Under stirring conditions of 500 rpm / min, solutions A and B were slowly added dropwise to deionized water. The pH value of the reaction system was controlled to be 11.5 and the system temperature was 55°C. After reacting for 20 hours, the obtained precipitate was washed, filtered and dried to obtain a lithium-rich manganese-based precursor Mn 0.54 Ni 0.13 Co 0.13 (OH)2.
[0092] According to the chemical formula Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 Nb 0.02 F 0.02 O 2.045 Weigh the corresponding amount of lithium-rich manganese-based precursor, lithium carbonate (in terms of Li), niobium oxide (in terms of Nb), and ammonium fluoride, put the above materials into a high-speed mixer, mix them evenly and press them into sheets, place them in an atmosphere furnace for sintering, the sintering atmosphere is air, first heat up to 500°C at a heating rate of 3°C / min, keep warm for 5 hours, then continue to heat up to 950°C at the same rate, keep warm for 15 hours, and cool to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0093] Example 8
[0094] This embodiment provides a single crystal lithium-rich manganese-based positive electrode material, whose chemical formula is Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 W 0.0 1F 0.07 O2.
[0095] The preparation method of the positive electrode material comprises the following steps:
[0096] Manganese sulfate monohydrate, nickel sulfate hexahydrate and cobalt sulfate heptahydrate were weighed in a molar ratio of 0.54:0.13:0.13, and dissolved in deionized water to prepare a 2 mol / L metal salt solution A; sodium hydroxide was dissolved in water to prepare a 2 mol / L precipitant solution B. Under stirring at 500 rpm / min, solutions A and B were slowly added dropwise to deionized water. The pH value of the reaction system was controlled to be 11.5 and the system temperature was 55°C. After reacting for 20 hours, the obtained precipitate was washed, filtered and dried to obtain a lithium-rich manganese-based precursor Mn. 0.54 Ni 0.13 Co 0.13 (OH)2.
[0097] According to the chemical formula Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 W 0.01 F 0.07 O2 weighs the corresponding amount of lithium-rich manganese-based precursor, lithium carbonate (in terms of Li, accounting for 85% of the amount of lithium added), lithium nitrate (in terms of Li, accounting for 15% of the amount of lithium added), tungsten oxide (in terms of W), and ammonium fluoride, puts the above materials into a high-speed mixer, mixes them evenly and presses them into sheets, which are placed in an atmosphere furnace for sintering. The sintering atmosphere is air, and the temperature is first increased to 500°C at a heating rate of 3°C / min, and then kept warm for 5 hours, and then continued to be heated to 950°C at the same rate, kept warm for 15 hours, and cooled to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0098] Example 9
[0099] This embodiment provides a single crystal lithium-rich manganese-based positive electrode material, whose chemical formula is Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 W 0.0 5F 0.01 O 2.15 .
[0100] The preparation method of the positive electrode material comprises the following steps:
[0101] Manganese sulfate monohydrate, nickel sulfate hexahydrate and cobalt sulfate heptahydrate were weighed in a molar ratio of 0.54:0.13:0.13, and dissolved in deionized water to prepare a 2 mol / L metal salt solution A; sodium hydroxide was dissolved in water to prepare a 2 mol / L precipitant solution B. Under stirring at 500 rpm / min, solutions A and B were slowly added dropwise to deionized water. The pH value of the reaction system was controlled to be 11.5 and the system temperature was 55°C. After reacting for 20 hours, the obtained precipitate was washed, filtered and dried to obtain a lithium-rich manganese-based precursor Mn. 0.54 Ni 0.13 Co0.13 (OH)2.
[0102] According to the chemical formula Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 W 0.05 F 0.01 O 2.15 Weigh the corresponding amount of lithium-rich manganese-based precursor, lithium carbonate (in terms of Li), tungsten oxide (in terms of W), and ammonium fluoride, put the above materials into a high-speed mixer, mix them evenly and press them into sheets, place them in an atmosphere furnace for sintering, the sintering atmosphere is air, first heat up to 500°C at a heating rate of 3°C / min, keep warm for 5h, then continue to heat up to 950°C at the same rate, keep warm for 15h, and cool to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0103] Example 10
[0104] This embodiment provides a single crystal lithium-rich manganese-based positive electrode material, whose chemical formula is Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 W 0.0 3F 0.02 O 2.085 .
[0105] The preparation method of the positive electrode material comprises the following steps:
[0106] Manganese sulfate monohydrate, nickel sulfate hexahydrate and cobalt sulfate heptahydrate were weighed in a molar ratio of 0.54:0.13:0.13, and dissolved in deionized water to prepare a 2 mol / L metal salt solution A; sodium carbonate was dissolved in water to prepare a 2 mol / L precipitant solution B. Under stirring at 500 rpm / min, solutions A and B were slowly added dropwise to deionized water. The pH value of the reaction system was controlled to be 8.5 and the system temperature was 50°C. After reacting for 20 hours, the obtained precipitate was washed, filtered and dried to obtain a lithium-rich manganese-based precursor Mn. 0.54 Ni 0.13 Co 0.13 CO3.
[0107] According to the chemical formula Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 W 0.03 F 0.02 O 2.085Weigh the corresponding amount of lithium-rich manganese-based precursor, lithium carbonate (in terms of Li), tungsten oxide (in terms of W), and ammonium fluoride, put the above materials into a high-speed mixer, mix them evenly and press them into sheets, place them in an atmosphere furnace for sintering, the sintering atmosphere is air, first heat up to 500°C at a heating rate of 3°C / min, keep warm for 5h, then continue to heat up to 950°C at the same rate, keep warm for 15h, and cool to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0108] Embodiment 11
[0109] This embodiment provides a single crystal lithium-rich manganese-based positive electrode material, whose chemical formula is Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 W 0.0 3F 0.02 O 2.085 .
[0110] The preparation method of the positive electrode material comprises the following steps:
[0111] Manganese sulfate monohydrate, nickel sulfate hexahydrate and cobalt sulfate heptahydrate were weighed in a molar ratio of 0.54:0.13:0.13, and dissolved in deionized water to prepare a 2 mol / L metal salt solution A; sodium hydroxide was dissolved in water to prepare a 2 mol / L precipitant solution B. Under stirring conditions of 500 rpm / min, solutions A and B were slowly added dropwise to deionized water. The pH value of the reaction system was controlled to be 11.5 and the system temperature was 55°C. After reacting for 20 hours, the obtained precipitate was washed, filtered and dried to obtain a lithium-rich manganese-based precursor Mn 0.54 Ni 0.13 Co 0.13 (OH)2.
[0112] According to the chemical formula Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 W 0.03 F 0.02 O 2.085 Weigh the corresponding amount of lithium-rich manganese-based precursor, lithium carbonate (in terms of Li), tungsten oxide (in terms of W), and ammonium fluoride, put the above materials into a high-speed mixer, mix them evenly and press them into sheets, place them in an atmosphere furnace for sintering, the sintering atmosphere is air, first heat up to 500°C at a heating rate of 3°C / min, keep warm for 5h, then continue to heat up to 800°C at the same rate, keep warm for 15h, and cool to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0113] Example 12
[0114] This embodiment provides a single crystal lithium-rich manganese-based positive electrode material, whose chemical formula is Li1.2 Mn 0.54 Ni 0.13 Co 0.13 W 0.0 3F 0.02 O 2.085 .
[0115] The preparation method of the positive electrode material comprises the following steps:
[0116] Manganese sulfate monohydrate, nickel sulfate hexahydrate and cobalt sulfate heptahydrate were weighed in a molar ratio of 0.54:0.13:0.13, and dissolved in deionized water to prepare a 2 mol / L metal salt solution A; sodium hydroxide was dissolved in water to prepare a 2 mol / L precipitant solution B. Under stirring conditions of 500 rpm / min, solutions A and B were slowly added dropwise to deionized water. The pH value of the reaction system was controlled to be 11.5 and the system temperature was 55°C. After reacting for 20 hours, the obtained precipitate was washed, filtered and dried to obtain a lithium-rich manganese-based precursor Mn 0.54 Ni 0.13 Co 0.13 (OH)2.
[0117] According to the chemical formula Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 W 0.03 F 0.02 O 2.085 Weigh the corresponding amount of lithium-rich manganese-based precursor, lithium carbonate (in terms of Li), tungsten oxide (in terms of W), and ammonium fluoride, put the above materials into a high-speed mixer, mix them evenly and press them into sheets, place them in an atmosphere furnace for sintering, the sintering atmosphere is air, first heat up to 500°C at a heating rate of 3°C / min, keep warm for 5h, then continue to heat up to 1100°C at the same rate, keep warm for 15h, and cool to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0118] Example 13
[0119] This embodiment provides a single crystal lithium-rich manganese-based positive electrode material, whose chemical formula is Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 Zr 0.02 Br 0.02 O 2.035 .
[0120] The preparation method of the positive electrode material comprises the following steps:
[0121] Manganese sulfate monohydrate, nickel sulfate hexahydrate and cobalt sulfate heptahydrate were weighed in a molar ratio of 0.54:0.13:0.13, and dissolved in deionized water to prepare a 2 mol / L metal salt solution A; sodium hydroxide was dissolved in water to prepare a 2 mol / L precipitant solution B. Under stirring at 500 rpm / min, solutions A and B were slowly added dropwise to deionized water. The pH value of the reaction system was controlled to be 11.5 and the system temperature was 55°C. After reacting for 20 hours, the obtained precipitate was washed, filtered and dried to obtain a lithium-rich manganese-based precursor Mn. 0.54 Ni 0.13 Co 0.13 (OH)2.
[0122] According to the chemical formula Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 Zr 0.02 Br 0.02 O 2.035 Weigh the corresponding amount of lithium-rich manganese-based precursor, lithium carbonate (in terms of Li), zirconium oxide (in terms of Zr), and ammonium bromide, put the above materials into a high-speed mixer, mix them evenly and press them into sheets, and directly place them in an atmosphere furnace for sintering. The sintering atmosphere is air. First, heat the temperature to 500°C at a heating rate of 3°C / min, keep it warm for 5 hours, then continue to heat it to 950°C at the same rate, keep it warm for 15 hours, and cool it to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0123] Embodiment 14
[0124] This embodiment provides a single crystal lithium-rich manganese-based positive electrode material, whose chemical formula is Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 Ta 0.02 Cl 0.02 O 2.045 .
[0125] The preparation method of the positive electrode material comprises the following steps:
[0126] Manganese sulfate monohydrate, nickel sulfate hexahydrate and cobalt sulfate heptahydrate were weighed in a molar ratio of 0.54:0.13:0.13, and dissolved in deionized water to prepare a 2 mol / L metal salt solution A; sodium hydroxide was dissolved in water to prepare a 2 mol / L precipitant solution B. Under stirring conditions of 500 rpm / min, solutions A and B were slowly added dropwise to deionized water. The pH value of the reaction system was controlled to be 11.5 and the system temperature was 55°C. After reacting for 20 hours, the obtained precipitate was washed, filtered and dried to obtain a lithium-rich manganese-based precursor Mn 0.54 Ni 0.13 Co 0.13(OH)2.
[0127] According to the chemical formula Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 Ta 0.02 Cl 0.02 O 2.045 Weigh the corresponding amount of lithium-rich manganese-based precursor, lithium carbonate (in terms of Li), tantalum oxide (in terms of Ta), and ammonium chloride, put the above materials into a high-speed mixer, mix them evenly and press them into sheets, and directly place them in an atmosphere furnace for sintering. The sintering atmosphere is air. First, heat the temperature to 500°C at a heating rate of 3°C / min, keep it warm for 5 hours, then continue to heat it to 950°C at the same rate, keep it warm for 15 hours, and cool it to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0128] Embodiment 15
[0129] This embodiment provides a single crystal lithium-rich manganese-based positive electrode material, whose chemical formula is Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 Hf 0.03 Cl 0.02 O 2.055 .
[0130] The preparation method of the positive electrode material comprises the following steps:
[0131] Manganese sulfate monohydrate, nickel sulfate hexahydrate and cobalt sulfate heptahydrate were weighed in a molar ratio of 0.54:0.13:0.13, and dissolved in deionized water to prepare a 2 mol / L metal salt solution A; sodium hydroxide was dissolved in water to prepare a 2 mol / L precipitant solution B. Under stirring at 500 rpm / min, solutions A and B were slowly added dropwise to deionized water. The pH value of the reaction system was controlled to be 11.5 and the system temperature was 55°C. After reacting for 20 hours, the obtained precipitate was washed, filtered and dried to obtain a lithium-rich manganese-based precursor Mn. 0.54 Ni 0.13 Co 0.13 (OH)2.
[0132] According to the chemical formula Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 W 0.03 F 0.02 O 2.04Weigh the corresponding amount of lithium-rich manganese-based precursor, lithium carbonate (in terms of Li), hafnium oxide (in terms of Hf), and ammonium chloride, put the above materials into a high-speed mixer, mix them evenly and press them into sheets, and directly place them in an atmosphere furnace for sintering. The sintering atmosphere is air. First, heat the temperature to 500°C at a heating rate of 3°C / min, keep it warm for 5 hours, then continue to heat it to 950°C at the same rate, keep it warm for 15 hours, and cool it to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0133] Comparative Example 1
[0134] This comparative example provides a lithium-rich manganese-based positive electrode material, the chemical formula of which is Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2.
[0135] The preparation method of the positive electrode material comprises the following steps:
[0136] Manganese sulfate monohydrate, nickel sulfate hexahydrate and cobalt sulfate heptahydrate were weighed in a molar ratio of 0.54:0.13:0.13, and dissolved in deionized water to prepare a 2 mol / L metal salt solution A; sodium hydroxide was dissolved in water to prepare a 2 mol / L precipitant solution B. Under stirring conditions of 500 rpm / min, solutions A and B were slowly added dropwise to deionized water. The pH value of the reaction system was controlled to be 11.5 and the system temperature was 55°C. After reacting for 20 hours, the obtained precipitate was washed, filtered and dried to obtain a lithium-rich manganese-based precursor Mn 0.54 Ni 0.13 Co 0.13 (OH)2.
[0137] According to the chemical formula Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2 weighs the corresponding amount of lithium-rich manganese-based precursor and lithium carbonate (in terms of Li), puts the above materials into a high-speed mixer, mixes them evenly and presses them into sheets, and places them in an atmosphere furnace for sintering. The sintering atmosphere is air. First, the temperature is increased to 500°C at a heating rate of 3°C / min, and then kept warm for 5 hours, and then the temperature is continued to be increased to 950°C at the same rate, and kept warm for 15 hours. After cooling to room temperature, a conventional lithium-rich manganese-based positive electrode material is obtained.
[0138] Comparative Example 2
[0139] This comparative example provides a single crystal lithium-rich manganese-based positive electrode material, whose chemical formula is Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 W 0.0 3O 2.095 .
[0140] The preparation method of the positive electrode material comprises the following steps:
[0141] Manganese sulfate monohydrate, nickel sulfate hexahydrate and cobalt sulfate heptahydrate were weighed in a molar ratio of 0.54:0.13:0.13, and dissolved in deionized water to prepare a 2 mol / L metal salt solution A; sodium hydroxide was dissolved in water to prepare a 2 mol / L precipitant solution B. Under stirring conditions of 500 rpm / min, solutions A and B were slowly added dropwise to deionized water. The pH value of the reaction system was controlled to be 11.5 and the system temperature was 55°C. After reacting for 20 hours, the obtained precipitate was washed, filtered and dried to obtain a lithium-rich manganese-based precursor Mn 0.54 Ni 0.13 Co 0.13 (OH)2.
[0142] According to the chemical formula Li 1.2 Mn 0.5a Ni 0.13 Co 0.13 W 0.03 O 2.095 Weigh the corresponding amount of lithium-rich manganese-based precursor, lithium carbonate (in terms of Li), and tungsten oxide (in terms of W), put the above materials into a high-speed mixer, mix them evenly and press them into sheets, place them in an atmosphere furnace for sintering, the sintering atmosphere is air, first heat up to 500°C at a heating rate of 3°C / min, keep warm for 5 hours, then continue to heat up to 950°C at the same rate, keep warm for 10 hours, and cool to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0143] Comparative Example 3
[0144] This comparative example provides a single crystal lithium-rich manganese-based positive electrode material, whose chemical formula is Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 F 0.0 2O 1.995 .
[0145] The preparation method of the positive electrode material comprises the following steps:
[0146] Manganese sulfate monohydrate, nickel sulfate hexahydrate and cobalt sulfate heptahydrate were weighed in a molar ratio of 0.54:0.13:0.13, and dissolved in deionized water to prepare a 2 mol / L metal salt solution A; sodium hydroxide was dissolved in water to prepare a 2 mol / L precipitant solution B. Under stirring conditions of 500 rpm / min, solutions A and B were slowly added dropwise to deionized water. The pH value of the reaction system was controlled to be 11.5 and the system temperature was 55°C. After reacting for 20 hours, the obtained precipitate was washed, filtered and dried to obtain a lithium-rich manganese-based precursor Mn 0.54 Ni0.13 Co 0.13 (OH)2.
[0147] According to the chemical formula Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 F 0.02 O 1.995 Weigh the corresponding amount of lithium-rich manganese-based precursor, lithium carbonate (in terms of Li), and ammonium fluoride, place the above materials in a high-speed mixer, mix them evenly and press them into sheets, place them in an atmosphere furnace for sintering, the sintering atmosphere is air, first heat up to 500°C at a heating rate of 3°C / min, keep warm for 5h, then continue to heat up to 950°C at the same rate, keep warm for 10h, and cool to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0148] Comparative Example 4
[0149] This comparative example provides a single crystal lithium-rich manganese-based positive electrode material, whose chemical formula is Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 W 0.0 3B 0.05 O 2.17 .
[0150] The preparation method of the positive electrode material comprises the following steps:
[0151] Manganese sulfate monohydrate, nickel sulfate hexahydrate and cobalt sulfate heptahydrate were weighed in a molar ratio of 0.54:0.13:0.13, and dissolved in deionized water to prepare a 2 mol / L metal salt solution A; sodium hydroxide was dissolved in water to prepare a 2 mol / L precipitant solution B. Under stirring conditions of 500 rpm / min, solutions A and B were slowly added dropwise to deionized water. The pH value of the reaction system was controlled to be 11.5 and the system temperature was 55°C. After reacting for 20 hours, the obtained precipitate was washed, filtered and dried to obtain a lithium-rich manganese-based precursor Mn 0.54 Ni 0.13 Co 0.13 (OH)2.
[0152] According to the chemical formula Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 W 0.03 B 0.05 O 2.17Weigh the corresponding amount of lithium-rich manganese-based precursor, lithium carbonate (in terms of Li), tungsten oxide (in terms of W), and boric acid, put the above materials into a high-speed mixer, mix them evenly and press them into sheets, place them in an atmosphere furnace for sintering, the sintering atmosphere is air, first heat up to 500°C at a heating rate of 3°C / min, keep warm for 5h, then continue to heat up to 950°C at the same rate, keep warm for 15h, and cool to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0153] Comparative Example 5
[0154] This comparative example provides a lithium-rich manganese-based positive electrode material, the chemical formula of which is Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 W 0.03 F 0.0 2O 2.085 .
[0155] The preparation method of the positive electrode material comprises the following steps:
[0156] Manganese sulfate monohydrate, nickel sulfate hexahydrate and cobalt sulfate heptahydrate were weighed in a molar ratio of 0.54:0.13:0.13, and dissolved in deionized water to prepare a 2 mol / L metal salt solution A; sodium hydroxide was dissolved in water to prepare a 2 mol / L precipitant solution B. Under stirring at 500 rpm / min, solutions A and B were slowly added dropwise to deionized water. The pH value of the reaction system was controlled to be 11.5 and the system temperature was 55°C. After reacting for 20 hours, the obtained precipitate was washed, filtered and dried to obtain a lithium-rich manganese-based precursor Mn. 0.54 Ni 0.13 Co 0.13 (OH)2.
[0157] According to the chemical formula Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 W 0.03 F 0.02 O 2.085 Weigh the corresponding amount of lithium-rich manganese-based precursor, lithium carbonate (in terms of Li), tungsten oxide (in terms of W), and ammonium fluoride, put the above materials into a high-speed mixer and mix them evenly, and directly place them in an atmosphere furnace for sintering. The sintering atmosphere is air. First, heat the temperature to 500°C at a heating rate of 3°C / min, keep it warm for 5 hours, then continue to heat it to 950°C at the same rate, keep it warm for 15 hours, and cool it to room temperature to obtain a lithium-rich manganese-based positive electrode material.
[0158] Experimental example
[0159] 1. X-ray diffraction test and SEM test were performed on the positive electrode materials of Examples 1-3 and Comparative Examples 1-5.
[0160] Depend on Figure 1 It can be seen that the main diffraction peaks of the positive electrode materials of Examples 1 and 2 of the present invention are consistent with α3NaFeO2 with a space group of R3-m, and a weak superlattice diffraction peak appears in the range of 10-30°, indicating that it has a typical lithium-rich manganese-based layered structure and does not contain other impurities.
[0161] Depend on Figure 2 , Figure 3 and Figure 4 It can be seen from the SEM image that the morphology of the positive electrode material of the present invention is monodispersed single crystal particles with a median particle size D 50 1-10μm.
[0162] Depend on Figure 5 It can be seen that the positive electrode material of Example 3 of the present invention has a lithium-rich layered phase crystal structure and does not contain other impurity phases, while the positive electrode material of Comparative Example 4 contains impurity phases.
[0163] Depend on Figure 6 It can be seen that the crystal structure of the positive electrode material of Comparative Example 1 is similar to that of Example 1, and is also a pure lithium-rich manganese-based layered structure. Figure 7 It can be seen that the morphology of the positive electrode material of Comparative Example 1 is polycrystalline particles with a secondary spherical structure, the primary particles are flake-shaped, and the thickness of the flake layer is 200-300 nm.
[0164] Depend on Figure 8 It can be seen that the crystal structure of the positive electrode material of Comparative Example 2 is similar to that of Example 1, and is also a pure lithium-rich manganese-based layered structure. Fig. 9 It can be seen that the morphology of the positive electrode material of Comparative Example 2 is polycrystalline particles with a secondary spherical structure, the primary particles are flake-shaped and granular, and the thickness of the flake layer is 100-200 nm.
[0165] Depend on Fig.10 It can be seen that the morphology of the positive electrode material of Comparative Example 3 is divided into two categories, one is polycrystalline particles with a secondary spherical structure, and its primary particles are polyhedrons; the other is large particles with a particle size of more than 2 μm. Fig.11 It can be seen that the morphology of the positive electrode material of Comparative Example 4 is monodispersed single crystal particles with a median particle size D 50 1.5-2μm. Fig.12 It can be seen that the positive electrode material of Comparative Example 5 has an uneven morphology, most of which are polycrystalline particles with a secondary spherical structure, the primary particles of which are nearly spherical with a diameter of 100-200 nm, and a small number of which are single crystal particles with a diameter of more than 2 μm.
[0166] 2. The positive electrode materials of Examples 1-15 and Comparative Example 5 were subjected to the following electrochemical performance tests:
[0167] The positive electrode material, acetylene black, polyvinylidene fluoride and N-methylpyrrolidone are mixed to form a slurry, which is evenly coated on the surface of an aluminum foil to obtain a positive electrode plate; then, a lithium plate is used as a negative electrode plate, and a 1 mol / L lithium hexafluorophosphate ethylene carbonate (EC) and dimethyl carbonate (DMC) solution (the volume ratio of EC to DMC is 1:1) is used as an electrolyte, and the batteries are assembled in a glove box to obtain a lithium-ion battery.
[0168] The lithium-ion battery was tested for cycle performance using an electrochemical tester at a temperature of 25°C and a current density of 0.1C (1C = 200 mAg -1 ), the charge and discharge voltage range is 4.8~2.0V, and the initial charge and discharge performance of the battery is tested. The cycle performance is tested at 2.0-4.8V, 1C / 1C system.
[0169] The test results are shown in Table 1 below.
[0170] Table 1 Electrochemical performance of positive electrode materials of Examples 1-15 and Comparative Example 5
[0171]
[0172]
[0173] It can be seen from the experimental results in Table 1 that the compaction density of the single crystal lithium-rich manganese-based positive electrode material of the present invention is 3.0 g / cm 3 Above, up to 3.6g / cm 3 , the specific surface area is 0.8m 2 / g or less, the lowest is only 0.25m 2 / g, which can greatly reduce the contact area between the positive electrode material and the electrolyte, thereby inhibiting the interface side reaction, and improving the volume energy density and cycle life of the lithium-rich manganese-based positive electrode material. The battery prepared using the positive electrode material of the present invention has an initial charge capacity of more than 310mAh / g, an initial discharge capacity of more than 240mAh / g, an initial coulombic efficiency of more than 76%, and a 500-week capacity retention rate of more than 89%.
[0174] According to the experimental results of Example 1, Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 in Table 1, combined with Fig.13 and Fig.14 It can be seen from the results that the addition of M element and N element in the single crystal lithium-rich manganese-based positive electrode material of the present invention has an important influence on the compaction density and specific surface area of the positive electrode material of the present invention. Removing one or both of the M element and the N element will reduce the compaction density and increase the specific surface area, thereby affecting the volume energy density and cycle life of the lithium-rich manganese-based positive electrode material.
[0175] Combination of Example 3 and Comparative Example 4 in Table 1 Fig.15 and Fig.16 It can be seen from the experimental results that if d+e≥0.08 during the preparation process of a single-crystal lithium-rich manganese-based positive electrode material of the present invention, the first lithium source and the second lithium source need to be added at the same time, which is conducive to reducing the compaction density of the positive electrode material and increasing the specific surface area, thereby improving the volume energy density and cycle life of the lithium-rich manganese-based positive electrode material. It can be seen from the experimental results of Comparative Example 5 that the mixture of the present invention needs to be pressed before high-temperature sintering, which is conducive to denser contact of the raw materials, more conducive to solid-phase reaction and crystal growth during the sintering process, and the obtained material has better uniformity, which is more conducive to forming single crystals with good dispersibility and uniform particle size, thereby reducing the compaction density of the positive electrode material and increasing the specific surface area.
[0176] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A single crystal lithium-rich manganese-based positive electrode material, characterized in that: The chemical formula of the positive electrode material is Li x Mn a Ni b Co c M d N e O g , wherein M is one of W, Mo, La, Zr, Nb, Ta, V, and Hf, N is one of F, B, Cl, and Br, 1<x≤1.2, 0.5<a≤0.6, 0.1≤b<0.15, 0.1<c≤0.15, 0.01≤d≤0.05, 0.01≤e≤0.07, 2≤g<2.2, 0.1≤d / e≤5; the positive electrode material has a lithium-rich layered phase crystal structure; The preparation method of the positive electrode material comprises the following steps: Step (1): dissolving a soluble manganese salt, a soluble nickel salt and a soluble cobalt salt in water to prepare a metal salt solution according to the chemical formula of the positive electrode material, controlling the temperature and pH value of the reaction system, adding a precipitant and a complexing agent to carry out a precipitation reaction, and washing, filtering and drying after the precipitation reaction to obtain a lithium-rich manganese-based precursor; Step (2): weighing corresponding amounts of the lithium-rich manganese-based precursor, the first additive containing the M element, the second additive containing the N element and the lithium source according to the chemical formula, mixing them evenly and then pressing to obtain a mixture; wherein, if d+e in the chemical formula of the positive electrode material is ≥0.08, at least two lithium sources need to be added, and the at least two lithium sources include a first lithium source and a second lithium source; if d+e<0.08, the second lithium source does not need to be added in step (2); Step (3): sintering the mixture obtained in step (2) at high temperature to obtain the positive electrode material; In step (2), the first lithium source is at least one of lithium carbonate, lithium hydroxide, and lithium chloride; The second lithium source is lithium nitrate; Calculated in terms of Li, the molar ratio of the amount of the lithium source added to the lithium-rich manganese-based precursor is 1:1 to 1.3:
1.
2. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following characteristics (1)-(3): (1) The morphology of the positive electrode material is monodispersed single crystal particles with a median particle size D 50 1μm-10μm; (2) The specific surface area of the positive electrode material is ≤1m 2 / g; (3) The compaction density of the positive electrode material is 3.0 g / cm 3 -3.6g / cm 3 .
3. The method for preparing the positive electrode material according to claim 1 or 2, characterized in that: The steps include: Step (1): dissolving a soluble manganese salt, a soluble nickel salt and a soluble cobalt salt in water to prepare a metal salt solution according to the chemical formula of the positive electrode material, controlling the temperature and pH value of the reaction system, adding a precipitant and a complexing agent to carry out a precipitation reaction, and washing, filtering and drying after the precipitation reaction to obtain a lithium-rich manganese-based precursor; Step (2): weighing corresponding amounts of the lithium-rich manganese-based precursor, the first additive containing the M element, the second additive containing the N element and the lithium source according to the chemical formula, mixing them evenly and then pressing to obtain a mixture; wherein, if d+e in the chemical formula of the positive electrode material is ≥0.08, at least two lithium sources need to be added, and the at least two lithium sources include a first lithium source and a second lithium source; if d+e<0.08, the second lithium source does not need to be added in step (2); Step (3): sintering the mixture obtained in step (2) at high temperature to obtain the positive electrode material.
4. The preparation method according to claim 3, characterized in that: In step (2), the first lithium source is at least one of lithium carbonate, lithium hydroxide and lithium chloride.
5. The preparation method according to claim 3, characterized in that: In step (2), the second lithium source is lithium nitrate.
6. The preparation method according to claim 3, characterized in that: In step (2), the molar ratio of the amount of the lithium source added to the lithium-rich manganese-based precursor is 1:1 to 1.3:1, calculated as Li.
7. The preparation method according to claim 3, characterized in that: In step (2), the pressing pressure is ≥ 0.05 MPa.
8. The preparation method according to claim 3, characterized in that: In step (2), the first additive containing the element M is one of tungsten oxide, molybdenum oxide, lanthanum oxide, zirconium oxide, niobium oxide, tantalum oxide, vanadium oxide, hafnium oxide, lithium tungstate, lithium molybdate, lithium lanthanate, lithium zirconate, lithium niobate, lithium tantalate, and lithium vanadate.
9. The preparation method according to claim 3, characterized in that: The second additive containing the N element is one of lithium fluoride, ammonium fluoride, boric acid, ammonium chloride, boric oxide, and ammonium bromide.
10. The preparation method according to claim 3, characterized in that: In step (3), the high-temperature sintering atmosphere is an oxygen-containing atmosphere, and the sintering system is firstly to increase the temperature to 400°C-700°C at a rate of 0.1°C / min-10°C / min, keep the temperature for 2h-10h, then increase the temperature to 800°C-1100°C at a rate of 0.1°C / min-10°C / min, keep the temperature for 5h-20h, and then naturally cool, crush and sieve to obtain the positive electrode material.
11. The preparation method according to claim 3, characterized in that: In step (1), the soluble manganese salt includes one or more of the sulfate, nitrate, acetate and chloride of manganese element.
12. The preparation method according to claim 3, characterized in that: The soluble nickel salt includes one or more of sulfate, nitrate, acetate and chloride of nickel element.
13. The preparation method according to claim 3, characterized in that: The soluble cobalt salt includes one or more of sulfate, nitrate, acetate and chloride of the cobalt element.
14. The preparation method according to claim 3, characterized in that: The precipitant is at least one of sodium hydroxide, potassium hydroxide, sodium carbonate and potassium carbonate.
15. The preparation method according to claim 3, characterized in that: The complexing agent is at least one of ammonia water, citric acid and oxalic acid.
16. The preparation method according to claim 3, characterized in that: The temperature of the precipitation reaction is 40-70°C.
17. The preparation method according to claim 3, characterized in that: When the precipitant is sodium hydroxide or potassium hydroxide, the pH value of the precipitation reaction is 9-12.
18. A lithium ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the positive electrode material according to claim 1 or 2 or the positive electrode material prepared by the preparation method according to any one of claims 3 to 17.
Citation Information
Patent Citations
High-compaction micron single crystal lithium-rich manganese-based positive electrode material, preparation method and lithium battery
CN116143200A
Tantalum and zirconium co-doped cobalt-free single crystal lithium-rich manganese-based positive electrode material and preparation method thereof
CN116623295A
Monocrystal lithium-manganese-rich positive electrode material for lithium ion battery and preparation method thereof
CN116632218A
Rich-lithium manganese-based composite material codoped with anions and cations and preparation method thereof
CN109904425A
Tungsten and sulfur co-doped modified lithium-rich manganese-based positive electrode material and preparation method thereof
CN113451582A
Cited By
Lithium-manganese-rich positive electrode material with annual ring structure as well as preparation method and application of lithium-manganese-rich positive electrode material
CN121583864A